Principle and prerequisites of regenerative agriculture: a review - Hanifah, Vyta W.; Karolinoerita, Vicca; Cahyana, Destika; Minasny, Budiman (Journal of Smart Agriculture and Environmental Technology, 2025)
Regenerative agriculture has recently gained popularity as a promising approach to achieving sustainable agriculture and ensuring food security. This article reviews scientific papers published between 1986 and 2024, as well as popular media, including the documentary "Kiss the Ground," released by Netflix in 2020, which successfully introduced the concept of regenerative agriculture to a broader audience. The article explores the definition, principles, and prerequisites of regenerative agriculture and examines how this concept can be adapted in Indonesia, given the challenges faced by conventional agriculture and the potential for integration with digital technology. This study used 342 papers discussing regenerative agriculture and those related to regenerative agriculture terminology using the virtual tool map, Research Rabbit, and selected 10 most papers relevancies. The review concludes that regenerative agriculture essentially encompasses or aligns with previously established concepts, including agroecology, organic farming, conservation agriculture, climate-smart agriculture, and traditional agricultural systems often associated with environmentally friendly and sustainable practices. In the Indonesian context, farming systems like Subak in Bali, integrated farming in Java, and climate-smart farming in East Nusa Tenggara can be classified as forms of regenerative agriculture. However, the prerequisites for regenerative agriculture to produce commercial-scale yields may vary across different agroecosystems, as each has its specific needs.